Coupling 3D geomechanics to classical sedimentary basin modeling: From gravitational compaction to tectonics. (December 2021) - Brüch, A.; Colombo, D.; Frey, J.; Berthelon, J.; Cacas-Stentz, M.C.; Cornu, T.; Gout, C.
Abstract: Classical sedimentary basin simulators account for simplified geomechanical models that describe material compaction by means of phenomenological laws relating porosity to vertical effective stress. In order to overcome this limitation and to deal with a comprehensive poromechanical framework, an iterative coupling scheme between a basin modeling code and a mechanical finite element code is adopted. This work focuses on the porous material constitutive law specifically devised to couple 3D geomechanics to basin modeling. The sediment material is considered as an isotropic fully saturated poro-elastoplastic medium undergoing large irreversible strains. Special attention is given to the development of a hardening law capable of reproducing the same porosity evolution as provided by the standard basin simulator when the sediment material is submitted to gravitational compaction under oedometric conditions. A synthetic case is used to illustrate the ability of the proposed workflow to integrate horizontal deformations in the basin model as such effects cannot be captured by the simplified geomechanics of the standard basin code. The results obtained by the coupled simulation demonstrate that horizontal compression may significantly contribute to overpressure development and brittle failure of the basin seal rocks, highlighting the importance of a coupled approach to simulate complex tectonic history.